91.5k views
0 votes
-8(x+12)-8x=3(x-11)+2x

2 Answers

4 votes

Answer:

x = 5.72 repeating

Explanation:

first multiply the numbers outside of the parenthesis.

-8x - 96 -8x = 3x -33 + 2x

second we combine like terms.

-16x - 96 = 5x - 33

third we combine the x terms over the equal line.

- 96 = -11x - 33

fourth we add 33 to - 96.

- 63 = -11x

lastly we divide by 11

= 63 divided by 11 = 5. 72 repeating

User Elp
by
4.5k points
3 votes

Answer:

so the answer is x = -3

Explanation:

have a nice day!!

User Andy Krouwel
by
4.2k points